1998
DOI: 10.1073/pnas.95.10.5678
|View full text |Cite
|
Sign up to set email alerts
|

MMS2 , encoding a ubiquitin-conjugating-enzyme-like protein, is a member of the yeast error-free postreplication repair pathway

Abstract: Among the three Saccharomyces cerevisiae DNA repair epistasis groups, the RAD6 group is the most complicated and least characterized, primarily because it consists of two separate repair pathways: an error-free postreplication repair pathway, and a mutagenesis pathway. The rad6 and rad18 mutants are defective in both pathways, and the rev3 mutant affects only the mutagenesis pathway, but a yeast gene that is involved only in error-free postreplication repair has not been reported. We cloned the MMS2 gene from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
222
0
11

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(247 citation statements)
references
References 51 publications
11
222
0
11
Order By: Relevance
“…RAD6 has been demonstrated to function in the error-free repair pathway, and utilizes RAD6, RAD18, RAD5, Mms2 and Ubc13 (Ulrich and Jentsch, 2000). All these proteins have been shown to interact at least transiently (Broomfield et al, 1998;Ulrich and Jentsch, 2000;Torres-Ramos et al, 2002). RAD6-RAD18 dimers (Bailly et al, 1997;Xin et al, 2000) in the presence of REV3 or RAD30 have been implicated in error-prone lesion bypass (Roche et al, 1995;McDonald et al, 1997;Cejka et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…RAD6 has been demonstrated to function in the error-free repair pathway, and utilizes RAD6, RAD18, RAD5, Mms2 and Ubc13 (Ulrich and Jentsch, 2000). All these proteins have been shown to interact at least transiently (Broomfield et al, 1998;Ulrich and Jentsch, 2000;Torres-Ramos et al, 2002). RAD6-RAD18 dimers (Bailly et al, 1997;Xin et al, 2000) in the presence of REV3 or RAD30 have been implicated in error-prone lesion bypass (Roche et al, 1995;McDonald et al, 1997;Cejka et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The rad6Δ and rad18Δ mutations, the founding genes of the PRR pathway, displayed an epistatic relationship to exo1Δ ( Figure 1A) [11], suggesting that EXO1 functioned in PRR for MMS tolerance. As mentioned previously, PRR is composed of at least three genetically distinct sub-pathways: a checkpoint pathway; an errorfree pathway; and an error-prone pathway, defined by the genes RAD9 [9], MMS2 [30] and REV3 [10,31,32], respectively. We found that mms2Δ was epistatic to exo1Δ, but that both rad9Δ and rev3Δ were synergistic with exo1Δ (see Figure 1B-D) by epistasis analysis for MMS sensitivity.…”
Section: Epistasis Analysis Defines a Role For Exo1 In The Mms2 Errormentioning
confidence: 99%
“…However, unlike rev3, the mms2 mutant displays a massively increased spontaneous mutation rate and this increase is dependent on REV functions. Furthermore, the mms2 and rev3 mutations are synergistic with respect to DNA damage sensitivity and the double mutant is comparable to that of the rad18 single mutant [52,53]. Based on these analyses, a model was proposed in which the RAD6 pathway is composed of two independent subpathways: one is mediated by TLS that requires REV1, 3 and 7, whereas the other is mediated by error-free PRR that requires MMS2 [52].…”
Section: Ddt In Saccharomyces Cerevisiaementioning
confidence: 99%
“…An error-free branch within the RAD6 pathway had been proposed but not convincingly demonstrated until the identification and functional characterization of MMS2 [52]. The mms2 mutant is moderately sensitive to a broad range of DNA damaging agents, and epistasis analysis places MMS2 within the RAD6 pathway.…”
Section: Ddt In Saccharomyces Cerevisiaementioning
confidence: 99%
See 1 more Smart Citation